A replication plan for "Does social media reduce corruption?" (Information Economics and Policy, 2017) - Randall J. Hannum (Kiel Institute for the World Economy (IfW), 2017)
The importance of replicating economic research to improve the validity of findings has been the topic of an ongoing discussion, but there is not a consensus of what that means in practice. This article discusses a rationale for replicating a study and offers a plan of how one might go about approaching a replication of an actual study.
Keywords: B40; D73; 330; Replications; corruption